2008
DOI: 10.1007/s11910-008-0027-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and headaches

Abstract: Sleep has long been recognized to both provoke and relieve headache. Epidemiologic research has associated sleep disorders with more frequent and severe headaches. Chronic daily, awakening, and morning headache patterns are particularly suggestive of sleep disorders, including sleep-related breathing disorders, insomnia, circadian rhythm disorders, and parasomnias. Snoring and other indicators of sleep-disordered breathing are the most commonly studied and are particularly salient because of the potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 48 publications
2
53
0
3
Order By: Relevance
“…Chronic pain is often associated with impaired sleep [44][45][46][47][48][49][50]. However, impaired sleep can also alter pain perception, which can heighten the perceived pain severity [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic pain is often associated with impaired sleep [44][45][46][47][48][49][50]. However, impaired sleep can also alter pain perception, which can heighten the perceived pain severity [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, impaired sleep can also alter pain perception, which can heighten the perceived pain severity [51]. Sleep deprivation can trigger migraines and other headaches and increase their perceived pain intensity [49][50]52]. We previously noted that veterans with impaired sleep reported more severe pain [16].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms underlying the pathogenesis of headache in OSAS are night-time fluctuations of oxygen saturation during the night with hypercapnia, vasodilatation, increased intracranial pressure and impaired sleep quality. However, the exact mechanisms of headache pathogenesis in the disease remain controversial [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a signifi cant relationship between morning headaches and obstructive sleep apnea syndrome (OSAS) has been identifi ed [12,24]. In a sleep clinic sample, the apnea/hypopnea index and, dose-dependently, the nadir of nocturnal oxygen saturation were associated with the occurrence of morning headaches [18]. Most recently, Goksan and colleagues [6] reported that the nadir oxygen saturation during rapid eye movement and non-rapid eye movement sleep as well as the mean oxygen saturation during total sleep time was signifi cantly lower in patients with or without OSAS suff ering from morning headache as compared to patients without morning headache.…”
Section: Introductionmentioning
confidence: 99%
“…Achtundvierzig Personen gaben an, unter morgendlichen Kopfschmerzen zu leiden (Prävalenz = 5%). Verglichen mit den Kontrollen berichteten Personen mit morgendlichen Kopfschmerzen signifikant öfter von Tagesschläfrigkeit (50% vs. 18.8%, p = 0.003), Schwierigkeiten, untertags wach zu bleiben (47.9% vs. 18.8%, p = 0.019) und ungewolltem Einnicken (29.2% vs. 8.3%, p = 0.019). Darüberhinaus gaben Personen mit morgendlichen Kopfschmerzen eine signifi kant längere Einschlafl atenz (26.5 + 27.5 vs. 13.5 + 13.5 min, p = 0.005), signifikant öfter gestörten Schlaf (58.3% vs. 14.6%, p < 0.001), nächtliches Herumwälzen im Bett (50.0% vs. 8.0%, p < 0.001), Durchschlafstörungen (64.6% vs. 22.9%, p < 0.001) und das Symptom "unruhige Beine" (20.8% vs. 2.1%, p = 0.01) an.…”
unclassified